Pengaruh pengetahuan perpajakan, sosialisasi perpajakan, dan insentif pajak UMKM di masa pandemi Covid-19 terhadap kepatuhan wajib pajak UMKM di Kota Malang - Butet Raciti Sitorus; Pujo Gunarso (University of Merdeka Malang, 2023)
The research aims to determine the effect of tax knowledge, tax socialization, and tax incentives on UMKM in Malang City. The method used is quantitative method, using survey techniques through distributing questionnaires. The research population is UMKM taxpayers who are in the city of Malang, and the sample of this study is 94 people. Descriptive statistical data analysis techniques, multiple regression analysis, hypothesis testing, and the coefficient of determination. The results showed that tax knowledge, tax socialization had a significant positive effect on UMKM taxpayer compliance in Malang City while tax incentives had no significant effect.